Porcine B Cell Subset Responses to Toll-like Receptor Ligands - Braun, Roman Othmar; Python, Sylvie; Summerfield, Artur (Frontiers in Immunology, 2017)
Toll-like receptors (TLR) triggering of B cells are known to promote B cell expansion, differentiation of B cells into antibody-producing and memory cells, but the TLR responses of porcine B cells is poorly characterized. Therefore, this study investigated the response pattern of porcine B cell subsets to a large collection of TLR ligands and demonstrates that the TLR2 ligand Pam3Cys-SK4 and the TLR7/8 ligands gardiquimod and resiquimod are particularly efficient at inducing proliferation, CD25 and CCR7. This activation was also determined in B-cell subpopulations including a CD21+IgM+ subset, an IgG+ subset and two putative B1-like subsets, defined as CD21-IgMhighCD11R1+CD11c+CD14+ and CD21-IgMhigh CD11R1-CD11c+CD14- B cells. The latter two were larger and expressed higher levels of CD80/86 and spontaneous phospholipase C-2 phosphorylation. All porcine B-cell subsets were activated by TLR2, TLR7 and TLR9 ligands. Naïve and memory conventional B cells responded similar to TLR ligands. The CD11R1+ B1-like subset had the highest proliferative responses. While both B1-like subsets did not spontaneously secrete IgM, they were the only subsets to produce high-level of TLR-induced IgM. Similar to polyclonal IgM responses, memory B cells were efficiently induced to produce specific antibodies by CpG oligodinucleotide, resiquimod and to a weaker extend by Pam3Cys-SK4. Depletion of plasmacytoid dendritic cells (pDC) enhanced TLR-induced antibodies. The same set of TLR ligands also induced CD40 on cDCs, pDC and monocytes with the exception of TLR4 ligand being unable to activate pDC. Gardiquimod and resiquimod were particularly efficient at inducing CCR7 on pDCs. Porcine B cells expressed high levels of TLR7, but relatively little other TLR mRNA. Nevertheless, TLR2 on B cells was rapidly upregulated following stimulation, explaining the strong responses following stimulation. Subset-specific analysis of TLR expression demonstrated a comparable expression of TLR2, TLR7 and TLR9 in all B cell subsets, but TLR3 was restricted to B1-like cells, whereas TLR4 was only expressed on conventional B cells, although both at low levels. Altogether, our data describe porcine innate B1-like cells, and how different B cell subsets are involved in innate sensing.